(untitled) (International Journal of Engineering and Computer Science, 2023)
Inverter-based Operational Transconductance Ampliﬁers (OTAs) are versatile and friendly scalable analog circuit blocks. Especially for the new CMOS technological nodes, several recent applications have been extensively using them, ranging from Analog Front End (AFE) to analog-to-digital converters (ADC). This work tracks down the current advances in inverter-based OTAs design, comparing their basic fully differential structures, such as Nauta (N), Barthelemy (B), Vieru (V) and Mafredini (M) ones, and, in addition, mixing them up to propose new fully differential single-ended and two-stage hybrid versions. The new herein-proposed fully differential hybrid OTAs are the composition of Barthelemy/Nauta (B/N), Barthelemy/Manfredini (B/M), Nauta/Vieru (N/V), and Manfredini/Vieru (M/V) OTAs. All OTAs were designed using the same Global Foundries 90 nm Tanner 16.30 and their performances are compared for post-layout simulations.